Towards Hot-Carrier Photovoltaics in Nanowires with Epitaxially Defined Potential Barriers - Peterkes,Noah (2025)
In this work, we present the design, fabrication, and characterization of InAs-based nanowire heterostructures with epitaxially defined InP and GaAs potential barrier segments, aimed at understanding and demonstrating the functionality of a double-barrier nanowire heterostructure as a hot-carrier photovoltaic, in which InP and GaAs barriers encapsulate an InAs absorber region, where hot carriers are locally excited using plasmonic nanoantennas. Such a device is expected to enhance the quantum efficiency of nanowire-based hot-carrier photovoltaics by enabling energy- and carrier-selective charge extraction. First, the conduction band barrier heights of the InP and GaAs segments were experimentally determined using temperature-dependent current–voltage measurements and Arrhenius analysis based on thermionic emission. Barrier heights of ΦInP = 0.431 eV and ΦGaAs = 0.398 eV were extracted for the InP and GaAs barriers, respectively. For the optoelectronic characterization, a custom setup was built to perform IV measurements under light of controlled wavelength and polarization. First, single-barrier devices were characterized under global illumination, confirming that both InP and GaAs barriers allow for optically induced charge-carrier separation. Further, devices with plasmonic nanoantennas were investigated, which were shown to locally enhance absorption in the nanowire segment between the antennas under polarized light. In this context, InP single-barrier devices with nanoantennas exhibited a behavior consistent with internal photoemission across the full spectral range, suggesting a barrier height below 0.45 eV, in agreement with the aforementioned barrier height measurements. However, the GaAs single-barrier and the double-barrier device showed strong hysteresis and offset voltage fluctuations, attributed to parasitic capacitance in the measurement setup. Accordingly, no conclusive results regarding the characteristics and performance of these devices could be obtained. Although the full functionality of the double-barrier device could not yet be demonstrated, this study provides important insights into the potential barrier structure and confirms the ability of the individual barriers to separate charge carriers. It also supports the feasibility of employing plasmonic nanoantennas for absorption localization in the intended double-barrier device, advancing the path toward higher-efficiency hot-carrier photovoltaics beyond the Shockley-Queisser limit.
Keywords: solid state physics; solar energy conversion; hot carriers; III−V nanowire heterostructures; plasmonics; optoelectronics; master thesis